Development of high-sensitive, reproducible colloidal surface-enhanced Raman spectroscopy active substrate using silver nanocubes for potential biosensing applications - Matham, Murukeshan Vadakke (2016)
Surface-enhanced Raman spectroscopy (SERS) has emerged as one of the thrust research areas that could find potential applications in bio and chemical sensing. We developed colloidal SERS active substrate with excellent sensitivity and high reproducibility using silver nanocube (AgNC) synthesized via the solvothermal method. Finite-difference time-domain simulation was carried out in detail to visualize dipole generation in the nanocube during localized surface plasmon resonance and to locate the respective hot spots in AgNC responsible for the huge Raman enhancement. The prediction is verified by the SERS analysis of the synthesized nanocubes using Rhodamine 6G molecule. An excellent sensitivity with a detection limit of 10^−17  M and a very high enhancement factor of 1.2×10^8 confirms the “hot spots” in the nanocube. SERS activity is also carried out for crystal violet and for food adulterant Sudan I molecule. Finally, label-free DNA detection is performed to demonstrate the versatility of SERS as a potential biosensor.